THERMAL COUPLED NUMERICAL SIMULATION OF COLD EXTRUSION AND THE OPTIMUM DESIGN OF DIE FOR THE INTERFERENCE FIT - WANG LiBo; LIU Yu; WANG Yu; QIN Yi (Jixie qiangdu)
Cold extrusion technology is a kind of high precision,efficient,high quality and low cost advanced production technology,in the modern production plays an important role. With the appearance of new lubricant,the new die material,the large press machine,bulk cold extrusion forming with high static strength material become possible. Though simulation the process of cold extrusion of scm435 alloy steel with thermo mechanical coupling numerical method,from shrinkage fit,placing the workpiece,extrusion,unloading,ejection of the workpiece,to cooling down workpiece and springback. Researched the change of the pre stress in each stage of the process of forming and the influence of temperature on the pre stress. On this basis,a concept of non-uniform interference quantity through piecewise sleeve and specific Process implementation are put forward,and in the research,the stress of the whole process of the two different structure is studied by using FEM simulation.